2020
DOI: 10.2507/ijsimm19-1-502
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of a Flexible Manufacturing System Regarding Sustainability

Abstract: The presented manuscript deals with the impact of manufacturing flexibility on the sustainability justification of the manufacturing system, related to manufacturing sustainable social, environmental and financial impact. Such impact is not described in the research sphere. The complexity of the optimisation parameters is reflected in the multi-objective nature that can be evaluated with the use of the simulation study method. The manuscript presents a description of manufacturing flexibility modelling, with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…• Human resources managerial output in the articles that we consulted has not been a point of focus based on the influence of information flow characteristics, whereas according to Oluwatayo and Adetoro (2020), human resource management can influence the job engagement of employees and consequently the performance of the company. • Flexible manufacturing in shop floor based on information flow characteristics has not been considered as a research focus, whereas flexible manufacturing company or organization can be continuously efficient when predictable and unpredictable events related to consumers, markets, machines, and environment occur (Sushil 2017;Dey et al 2019;Shukla et al 2019;Singh et al 2019;Contador et al 2020;Evans and Bahrami 2020;Ojstersek et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…• Human resources managerial output in the articles that we consulted has not been a point of focus based on the influence of information flow characteristics, whereas according to Oluwatayo and Adetoro (2020), human resource management can influence the job engagement of employees and consequently the performance of the company. • Flexible manufacturing in shop floor based on information flow characteristics has not been considered as a research focus, whereas flexible manufacturing company or organization can be continuously efficient when predictable and unpredictable events related to consumers, markets, machines, and environment occur (Sushil 2017;Dey et al 2019;Shukla et al 2019;Singh et al 2019;Contador et al 2020;Evans and Bahrami 2020;Ojstersek et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since a poorly designed workplace can have longterm negative effects on the health of employees (musculoskeletal disorders -MSD), it is very important how a workplace is designed and organised (Edtmayr et al, 2011;Fritzsche et al, 2014;Kaljun, & Dolšak, 2012;Ojsteršek et al, 2020;Panush, 2017;Vujica Herzog & Harih, 2019;Wells et al, 2007). Short time movements are typical for the presented job of final quality control.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, firms are rushing to implement operational programs and best practices that have been successful in other firms [39]. Manufacturing firms are continuously trying to strengthen their competitive position by implementing AMT faster than their competitors [40]. Case studies have shown that AMT positively affect tangible (such as cost, inventory, etc.)…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%